Study on Method of Measuring Ionization Energy Loss of Time Projection Chamber Using UV Laser - CHANG Yue1, 2, QI Huirong2, 3, SHE Xin2, 3, ZHANG Jinxian2, 3, YU Chunxu1, ZHAO Guang2, 3, WU Linghui2, 3, DENG Zhi4, WANG Jianchun2, 3 (Yuanzineng kexue jishu)
The time projection chamber (TPC) is a critical component in collider physics, dark matter research, and nuclear physics due to its high precision, low material budget, and superior particle identification (PID) capabilities. The TPC’s main strength is its ability to measure both the ionization energy loss (dE/dx) and the momentum of particles simultaneously, which is essential for accurate ionization energy loss measurement and PID. However, traditional methods for measuring ionization energy loss, such as charged particle beams or cosmic rays, are not only expensive but also suffer from low repeatability. UV lasers present a cost-effective, portable, and flexible alternative to these traditional particle beams. By adjusting the laser energy, the ionization process can be easily controlled, allowing for precise simulations of different particle momentum. This capability is crucial for studying the dE/dx resolution of TPC and meeting various physical requirements. An innovative method that optimizes the probability density distribution of laser ionization was introduced. The method involved monitoring and adjusting the energy of each laser pulse, which significantly improves the measurement accuracy of dE/dx resolution. The experimental setup included a TPC prototype equipped with a double-layer gas electron multiplier (GEM) module and a laser optical path for validation purposes. The method entailed monitoring the energy of each laser pulse and making corrections to optimize the probability density distribution of laser ionization. This optimization was aimed at enhancing the measurement accuracy of dE/dx resolution. The test was conducted over 40 minutes, utilizing eight effective pad readout layers and retaining 43 000 events. The experimental results indicate that this method successfully recovers the Gaussian energy spectrum of monochromatic lasers, enabling precise measurement of dE/dx resolution. Additionally, the experiment involves stitching laser events to simulate the dE/dx resolution of the TPC at an effective length of 1.2 m. The simulated dE/dx resolution was calculated to be 4%, which aligns closely with the results of DESY GEM module beam test. This close alignment further substantiates the effectiveness of the proposed method in enhancing the measurement accuracy of dE/dx resolution. In order to explore the variables that influence the performance of TPC, an extensive simulation software framework for TPC was constructed, enabling swift and accurate performance simulations. This framework yields simulation data for the dE/dx parameter of large-scale TPC in environments with both zero and three Tesla magnetic fields. The research is of considerable importance to particle physics. It presents an innovative and streamlined technique for assessing ionization energy loss, which is a crucial factor in PID, and it also greatly aids in the energy profiling and distortion correction of TPC. This cutting-edge methodology enhances the versatility of TPC across different domains, including their use in collider experiments and dark matter investigations, and it also establishes a foundation for employing UV lasers in the energy and distortion analysis of TPC.